Preschoolers' self-regulation, skill differentials, and early educational outcomes - Johanna Sophie Quis; Anika Bela; Guido Heineck (Bamberg University, Bamberg Economic Research Group (BERG), 2018)
Are there skill differentials in young children's competence levels by their self-regulation abilities and do such early life differences mark the onset of increasing disparities in competence development? We add to previous research by investigating the relationship between preschoolers' self-regulation and their mathematical competence and its development early in primary school. We use data from the kindergarten cohort of the German National Educational Panel Study (NEPS) which provides observations of self-regulatory behavior as well as mathematical skills and allows controlling for a rich set of relevant background variables. Our results imply a positive association between children's self-regulation and their mathematical competence levels, even when holding general cognitive ability in kindergarten constant. Yet, self-regulation is not related to competence development over the first two years of primary school, meaning that the initial skill gap neither widens nor narrows substantially. Heterogeneity analyses indicate that self-regulation benefits children with low initial levels of mathematical competence at the transition from kindergarten to primary school. No growth gradient, however, is observable between grade 1 and grade 2.
Keywords: 330; Self-regulation; Skill formation; Competence development